(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of Italian tortricid moth, Cnephasia etnana sp.n. from Mount Etna, Sicily, is described. Extemally the new species resembles C. abrasana (Duponchel, 1843), or forms of C. constantinana Razowski, 1965, or C. korvaci Razowski, 1965. In male genitalia it is similar to the two last mentioned species, the differences are in the size of terminal plate of the gnathos (mainly in C. korvaci) and the smaller aedeagus; from C. abrasana it strongly differs in the structure of sacculus. The females of C. etnana and C. abrasana are very similar to one another mainly in the form of the ovipositor and papillae anales which are slenderer and more simple than in all known species of the subgenus Cnephasia s.str. inclusive the two compared species.